Is Next-Generation Sequencing the way to go for Residual Disease Monitoring in Acute Lymphoblastic Leukemia? - Kotrova, Michaela; Trka, Jan; Kneba, Michael; Brüggemann, Monika (Molecular diagnosis & therapy, 2017)
Minimal residual disease (MRD) is the most important independent prognostic factor in acute lymphoblastic leukemia (ALL). Since it has been implemented into in treatment stratification strategies, cure rates have improved significantly for all age groups. Real time quantitative (RQ)-PCR of clonal immunoglobulin and T-cell receptor gene rearrangements using allele-specific primers is currently regarded as the gold standard for MRD analysis in ALL, as it is not only highly sensitive and specific but also provides accurate MRD quantification. Following recent advances in next-generation sequencing (NGS), much attention has been devoted to the development of NGS-based MRD assays. This new technique can enhance sensitivity provided that sufficient numbers of cells are analyzed. Recent reports have shown that NGS-MRD also tends to be more specific for relapse prediction than RQ-PCR. In addition, NGS provides information on the physiological B- and T-cell repertoire during and after treatment, which has been shown to be prognostically relevant. However, before implementation of NGS-MRD detection in clinical practice, several issues must be addressed and the whole workflow needs to be standardized, including not only the analytical phase (spike-in calibrators, quality controls) but also the pre-analytical (e.g. sample preparation) and the post-analytical phases (e.g. bioinformatics pipeline, guidelines for correct data interpretation). These topics are currently addressed by a European network, the EuroClonality-NGS Consortium. In conclusion, NGS is a promising tool for MRD detection with the potential to overcome most of the limitations of RQ-PCR and to become the new gold standard for MRD detection in ALL.
Keywords: Neoplasm, Residual; Male; Multicolor Flow Cytometry; High-Throughput Nucleotide Sequencing; Minimal Residual Disease; prognóza; Sequence Analysis, DNA; sekvenční analýza DNA; mužské pohlaví; Marker Identification; akutní lymfatická leukemie; receptory antigenů T-buněk; Receptors, Antigen, T-Cell; lidé; Minimal Residual Disease Detection; ženské pohlaví; Humans; vysoce účinné nukleotidové sekvenování; reziduální nádor; Acute Lymphoblastic Leukemia; Prognosis; Female; Precursor Cell Lymphoblastic Leukemia-Lymphoma